Emergence and Persistence of High-Risk Clones Among MDR and XDR A. baumannii at a Brazilian Teaching Hospital - Tavares, Laís Calissi Brisolla; Vasconcellos, Francielli Mahnic de; Sousa, William Vaz de; Rocchetti, Taisa Trevizani; Mondelli, Alessandro Lia; Ferreira, Adriano Martison; Montelli, Augusto Cezar; Sadatsune, Terue; Tiba-Casas, Monique Ribeiro; Camargo, Carlos Henrique (Frontiers in Microbiology, 2019)
Dissemination of carbapenem-resistant Acinetobacter baumannii is currently one of the priority themes discussed around the world, including in Brazil, where this pathogen is considered endemic. A total of 107 carbapenem-resistant A. baumannii (CRAB) isolates were collected from patients with bacteraemia attended at a teaching hospital in Brazil from 2008 to 2014. From these samples, 104 (97.2%) carried blaOXA-23-like, all of them associated with ISAba1 The blaOXA-231 (1.9%) and blaOXA-72 (0.9%) genes were also detected in low frequencies. All isolates were susceptible to minocycline, and 38.3% of isolates presented intermediate susceptibility to tigecycline (MIC = 4μg/ml). Molecular typing assessed by multi-locus sequence typing demonstrated that the strains were mainly associated with clonal complexes CC79 (47.4%), followed by CC1 (16.9%), and CC317 (18.6%), belonging to different pulsotypes and in different prevalences over the years. Changes in the clones’ prevalence reinforce the need of identifying and controlling CRAB in hospital settings to preserve the already scarce therapeutic options available.